Formation of the Image of "I" of Preschool Children on the Basis of Uzbek Folk Tales and Preparation of the Child for School in the Organization of Preschool Education on the Basis of Requirements of Preschool Education - Karimovich, Muminov Shermat (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to the formation of the image of "I" in preschool education based on Uzbek folk tales, as well as the preparation of a child for school in preschool education in accordance with the requirements of preschool education.